Case-Based Belief Formation under Ambiguity - Jürgen Eichberger; Ani Guerdjikova (Verein für Socialpolitik, 2010)
In this paper, we consider a decision-maker who tries to learn the distribution of outcomes from previously observed cases. For each observed database of cases the decision-maker predicts a set of priors expressing his beliefs about the underlying probability distribution. We impose a version of the concatenation axiom introduced in BILLOT, GILBOA, SAMET, AND SCHMEIDLER (2005) which ensures that the sets of priors can be represented as a weighted sum of the observed frequencies of cases. The weights are the uniquely determined similarities between the observed cases and the case under investigation. The predicted probabilities, however, may vary with the number of observations. This generalisation of BILLOT, GILBOA, SAMET, AND SCHMEIDLER (2005) allows one to model learning processes.
Keywords: D81; D83; D80; 330; case-based decision theory; ambiguity; multiple priors; learning; similarity